Bibliometric Innovation: Towards Work Training Literature In The Era Of Digital Development - Sucipto, Imam; Kusumah, Dadang Heri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The development of digital technology has had a significant impact on various aspects of life, including work training. In facing this digital era, bibliometric analysis has become a key tool for understanding the evolution of work training literature. This research proposes bibliometric innovations related to work training literature in the era of digital development. By utilizing bibliometric techniques, this research creates a roadmap illustrating trends, contributions, and collaboration patterns in the work training literature. The results of this bibliometric analysis provide an in-depth understanding of changes in work training literature triggered by the digital era. These findings can provide valuable guidance for researchers, practitioners, and policymakers to design training strategies that are responsive to technological developments. In conclusion, bibliometric innovation in the work training literature in the digital era provides a strong foundation for understanding the dynamics and capturing innovation opportunities in the context of future workforce training.